Biofilm Formation by Pseudallescheria/Scedosporium Species: A Comparative Study - Rollin-Pinheiro, Rodrigo; de Meirelles, Jardel V.; Vila, Taissa V. M.; Fonseca, Beatriz B.; Alves, Vinicius; Frases, Susana; Rozental, Sonia; Barreto-Bergter, Eliana (Frontiers in Microbiology, 2017)
Pseudallescheria/Scedosporium species are medically important fungi that are present in soil and human impacted areas and capable of causing a wide spectrum of diseases in humans. Although little is known about their pathogenesis, their growth process and infection routes are very similar to those of Aspergillus species, which grow as biofilms in invasive infections. All nine strains tested here displayed the ability to grow as biofilms in vitro and to produce a dense network of interconnected hyphae on both polystyrene and the surfaces of central venous catheters, but with different characteristics. S. boydii and S. aurantiacum clinical isolates were able to form biofilms faster than the corresponding environmental strains, as evidenced in kinetic assays for S. boydii and CLSM for S. aurantiacum. Biofilms formed by Pseudallescheria/Scedosporium species had significantly higher resistance to the class of antifungal azole than was observed in planktonic cells, indicating a protective role for this structure. In addition, the clinical S. aurantiacum isolate that formed the most robust biofilms was also more virulent in a larvae Galleria mellonella infection model, suggesting that the ability to form biofilms enhances virulence in Pseudallescheria/Scedosporium species.